Animal models of attention‐deficit hyperactivity disorder (ADHD). Issue 2 (23rd January 2021) - Rahi, Vikrant; Kumar, Puneet
Abstract: Attention‐deficit hyperactivity disorder ( ADHD) is a heterogeneous neuropsychiatric disorder characterized by three primary symptoms hyperactivity, attention deficit, and impulsiveness, observed in both children and adults. In childhood, this disorder is more common in boys than in girls, and at least 75% will continue to suffer from the disorder until adulthood. Individuals with ADHD generally have poor academic, occupational, and social functioning resulting from developmentally inappropriate levels of hyperactivity and impulsivity, as well as impaired ability to maintain attention on motivationally relevant tasks. Very few drugs available in clinical practice altogether abolish the symptoms of ADHD, therefore, to find new drugs and target it is essential to understand the neuropathological, neurochemical, and genetic alterations that lead to the progression of ADHD. With this contrast, an animal study is the best approach because animal models provide relatively fast invasive manipulation, rigorous hypothesis testing, as well as it provides a better angle to understand the pathological mechanisms involved in disease progression. Moreover, animal models, especially for ADHD, serve with good predictive validity would allow the assessment and development of new therapeutic interventions, with this aim, the present review collect the various animal models on a single platform so that the research can select an appropriate model to pursue his study. Abstract : The review is based upon the animal models of attention‐deficit hyperactivity disorder (ADHD) a heterogeneous neuropsychiatric disorder. Three features (face, construct, and predictive validity) of Genetic and physical trauma models are targeted in the review, so that the researcher can select an appropriate model for study.